Innovations in Pharmacy through Practice-Based Research - Jean-Venable; William R. Doucette, PhD; Lawrence M. Brown, PharmD, PhD; Jon C. Schommer, PhD; Djenane Ramalho de Oliveira, PhD (University of Minnesota Libraries Publishing, 2010)
The overall purpose of this article is to serve as an invitation for submissions to the 'Practice-Based Research' section of INNOVATIONS in pharmacy. To provide background about this section of the journal, this paper describes: (1) the concept of innovations that we will apply, (2) the practice-based research domain, and (3) the use of practice-based research networks for this area of inquiry. We propose that uncertainty surrounding an innovation often will result in the postponement of the decision regarding its adoption until further evidence can be obtained. Such evidence often is gathered through considering the advice and experiences of opinion leaders and members of social systems who have adopted the innovation.We invite authors to present ideas, arguments, and evidence for innovations in pharmacy that arise out of practice-based research. We propose that this journal will be an excellent communication vehicle for providing convincing arguments and sound evidence in favor of innovations. Discourse regarding new ideas in such a format can further develop the ideas, create a critical mass of evidence, and be used for convincing others that the innovation should be adopted. We welcome submissions to the INNOVATIONS in pharmacy, PRACTICE-BASED RESEARCH content area that: (1) provide convincing arguments and sound evidence in favor of innovations for pharmacy, (2) are based upon practice-based research from case studies of single patients on one end of the continuum to findings from large populations of patients on the other end of the continuum, and/or(3) introduce innovations for practice-based research networks. We encourage articles from all perspectives and from all methods of inquiry.